Alliance Proximity and Effectiveness of Extended Deterrence. Issue 1 (2nd January 2018) - Bak, Daehee
ABSTRACT: This article examines whether geographical proximity between defensive allies and a protégé increases the likelihood of successful extended general deterrence. I argue that proximate allies are better at making a credible deterrent threat because proximate allies are more willing and able to help alliance partners in times of crisis than distant ones. This claim is theorized by examining how geographical distance influences the international and domestic costs of alliance commitments. The empirical tests reveal that a potential aggressor is less likely to initiate a militarized dispute against a target with proximate defensive allies. Furthermore, I find that the power of proximate defensive allies is a more significant determinant of successful extended general deterrence than that of distance allies. Interestingly, I also find that the constraining effects of geographical distance on the effectiveness of extended general deterrence have been alleviated by advancements in military technologies throughout history.